Cell site analysis: Changes to networks with time. Issue 3 (May 2022) - Tart, Matt
Abstract: Cell service areas may change over time as sites or cells are adjusted, decommissioned or introduced, and there may have been changes between the time of calls and the analysis undertaken. The manner in which survey data is used as part of an analysis is of particular relevance as the data gathered may not reflect the state of the network at the time of calls and thus potentially mislead. Overlaying "historic" data (potentially generated before the calls) with "targeted" surveys (usually generated after the calls) may enable an assessment of possible network changes, or whether additional cells may also have served at a given location at a previous time. This paper outlines a case in which there was a significant time gap between the analysis of call data records and the date on which they were generated.